The I’m Learning! intervention methodology for quality learning environments in developing country contexts - Ryall, Cameron; Zook, Lisa (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Within the context of the global learning crisis and calls to focus on the quality of education, one international organisation took a systematic and holistic approach to improve learning, wellbeing, and development in schools. Known as the Quality Learning Environment (QLE) Framework, it conceptualised the quality of the learning environment in schools with four guiding principles: emotional and psychological protection of learners, physical wellbeing of children, active learning processes, and close collaboration between school and parents/community. From 2013 – 2017, the framework was piloted in three countries of Cambodia, Uganda, and Zimbabwe to improve learning environments and outcomes while documenting the process, methods, and results of the QLE pilot in their country. The interventions in the three countries were closely tracked by a longitudinal research study. This paper explores the ambition of global and national research firms to carry out rigorous cross-country research alongside contextualized and evolving school interventions.